Treating Vulnerable Populations of Cancer Survivors: A Biopsychosocial Approach - Fitzpatrick, Tanya R. (Springer International Publishing : Imprint: Springer, 2016)
This competence-building resource synthesizes a rich trove of conceptual and practical information on treating cancer survivors at risk of being underserved. Spotlighting a diverse group of ethnic and other demographic populations surviving diverse forms of cancer, the book models the assessing of needs and the developing of strategies to meet them. The multiple burden of cancer-medical and psychosocial problems, discrimination and stigma, quality of life issues-is described in depth as it affects different cultural and age populations. Contributors also present interventions that effectively and meaningfully address these complex intersections of physical, emotional, interpersonal, and layered social concerns. Included among the topics: Providing psychosocial distress screening, coping resources and self-care to newly diagnosed cancer survivors. Latino cancer survivors: the old and the young. "immigrants'="" cancer="" experience="" and="" implications="" for="" supportive="" interventions.< Survivorship issues among Muslim women with cancer. How art therapy can benefit the quality of life of young breast cancer survivors. The family caregiver as cancer survivor: supporting and promoting positive bereavement outcomes. Unique among the survivor literature, Treating Vulnerable Populations of Cancer Survivors ably assists health psychologists, social workers, and nurses in providing services to patients facing special challenges during recovery.